Krusialnya Peran Orang Tua Meningkatkan Motivasi Belajar Anak - Wahyu Nurmalasari (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2025)
Learning motivation is a crucial factor in supporting children's knowledge acquisition. It directly impacts children, particularly regarding their academic performance. Low learning motivation represents a significant barrier to achieving educational goals. Parents are the first and most vital educators in their child's educational process. Consequently, parental roles are highly essential in fulfilling the immense responsibilities of personality development, skill enhancement, and household management. This study aims to describe the role of parents in increasing children's learning motivation. This research employs a qualitative method with a case study approach. Data collection was conducted through observation, interviews, and questionnaires. The data analysis techniques used were data reduction, data display, and conclusion drawing. Based on the research findings, the lack of parental involvement in motivating children's learning is caused by a shortage of available time and a sub-optimal understanding of the school subjects. Parents are suggested to take several actions to motivate and improve their children's learning outcomes, such as dedicating spare time to communicate with their children.